Overexpression of FOXO1 may suppress proliferation and migration and correlate with tumor immune cells in nasopharyngeal carcinoma - Yu, Peng; Wei, Wenyang; Wu, Guoqing; Liu, Xuexiang; Qin, Shini; Ma, Han; Feng, Leru; Cai, Yonglin; Liu, Limin (Translational Cancer Research, 2026)
Forkhead box protein O1 (FOXO1) is known to be dysregulated in multiple tumors and is significantly linked to tumor metastasis and invasion. Nevertheless, its role in the development and progression of nasopharyngeal carcinoma (NPC) remains poorly understood. This study aimed to examine alterations in FOXO1 expression in NPC and its effects on biological behavior.